"Machines to generate desire": Avant-garde Manifestos and Guerrilla Advertising - Hanna, Julian (2013)
The association between the avant-garde and advertising is longstanding and bidirectional. Advertising, after all, is one of the “shocks” of modernity described by Walter Benjamin in his writings on Baudelaire. Avant-garde art reproduces the primary urban shock effects of crowds, advertisements, and other stimuli. The manifesto has always functioned as an advertisement for artistic movements, as for political and social ones. In this study I examine the relationship between the historical avant-garde and contemporary non-traditional or “guerrilla” advertising and marketing strategies. The term “guerrilla” is used as shorthand for a variety of new strategies of consumer engagement, particularly those using social networks. Each section is inspired by a key term adopted (or co-opted) from the language of advertising and marketing.